Knowledge, Skill, and Mentoring System of Chairman on Influencing the Team Method Approach at Inpatient Room of Cengkareng Hospital - Febri Dian Morina; Endang Ruswanti; Kemala Rita Wahidi (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: The team often organizes nursing services to improve healthcare services. Objective: The study aims to obtain empirical evidence of the influence of the team leader's knowledge and skills on implementing the team method with the mentoring system as a moderating variable. Method: This study applied to the cross-sectional study. The population was the team leader who served in the inpatient installation of as many as 107 personnel. Result: The results found that knowledge, skills, and mentoring system among team leaders significantly affect the implementation of the team method. While partially only the mentoring system does not affect the effectiveness of the team method implementation, the mentoring system cannot moderate the relationship between team method knowledge and skills on the efficacy of team method implementation. Conclusion: Supposedly, to increase the effectiveness of implementing the team method, the head of the room as a manager would be better off if he only carried out the supervisory and control functions. Recommendation: The team leader needs to improve their knowledge and skills to implement the team method effectively. Further studies need to explore how mentoring system could improve the team approach using the mixed method study